1996
DOI: 10.1007/bf01986273
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus sorption capacity of low activity clay soils of South Western Nigeria and its usefulness in evaluating P requirement of rice

Abstract: Field and laboratory experiments were conducted on 15 low activity clay soils in Ogun State of Nigeria to evaluate the relationships between P sorption capacity and some soil properties and the use of sorption indices in evaluating the P requirement of rice. Langmuir adsorption capacity (b) varied from 30.9 to 414.3/zg g-l. Although adsorption capacity was related significantly to a number of soil properties, citrate dithinonite bicarbonate (CDB) extractable Fe was the most important variable accounting for 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
(14 reference statements)
1
4
0
Order By: Relevance
“…We also observed that contrary to the single supply of S, the two single P rates resulted in significant higher dry matter yield in all the soils except Obantoko II, which already contained adequate nutrients and in Alabata II and III where 45 kg P ha -1 yielded high biomass only when S was applied. Increased maize grain yield to P application has been earlier reported from various studies in Nigeria (Adediran and Banjoko, 1995;Adetunji, 1997;Yusuf et al, 2003;Ayodele and Omotosho, 2008) and in other countries (Taalab et al, 2008;Wortmann et al, 2009). Similar observation on effect of P on maize grain yield has been reported for biomass yield.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We also observed that contrary to the single supply of S, the two single P rates resulted in significant higher dry matter yield in all the soils except Obantoko II, which already contained adequate nutrients and in Alabata II and III where 45 kg P ha -1 yielded high biomass only when S was applied. Increased maize grain yield to P application has been earlier reported from various studies in Nigeria (Adediran and Banjoko, 1995;Adetunji, 1997;Yusuf et al, 2003;Ayodele and Omotosho, 2008) and in other countries (Taalab et al, 2008;Wortmann et al, 2009). Similar observation on effect of P on maize grain yield has been reported for biomass yield.…”
Section: Discussionsupporting
confidence: 77%
“…Low soil P availability is well established in Nigeria (Adepetu, 1993). Application rate of 120 kg N ha -1 and 40 kg P ha -1 had significantly increased the growth and yield of maize in Southwestern Nigeria (Adetunji, 1997;Onasanya et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…between 42 and 175 mg kg y Table 3 . The SPR of soils 2, 3 and 7 were Ž higher than reported for some soils in West Africa Adetunji, 1997;Mokwunye . et al, 1986 , but the second group of soils had SPR within the range for most West African soils.…”
Section: Phosphorus Adsorptionmentioning
confidence: 58%
“…Volcanic soils have been extensively studied in the world, particularly with respect to phosphorus adsorption ( Van Ranst et al, 2004 ; Auxtero, Madeira & Sousa, 2008 ; Hashimoto et al, 2012 ; Valle et al, 2015 ), but there is a dearth of information on volcanic soils in Africa. A number of published papers address the phosphate sorption by African soils ( Sibanda & Young, 1986 ; Loganathan, Isirimah & Nwachuku, 1987 ; Frossard et al, 1992 ; Adepoju, 1993 ; Arduino et al, 1993 ; Adetunji, 1997 ; Henry & Smith, 2003 ; Nwoke et al, 2003 ; Gichangi, Mnkeni & Muchaonyerwa, 2008 ). A few papers deal with phosphate adsorption by African volcanic soils: Duffera & Robarge (1999) studied P sorption by four highland soils of Ethiopia, among which an Andosol developed from volcanic ash.…”
Section: Introductionmentioning
confidence: 99%